1987
DOI: 10.1085/jgp.89.4.541
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the basolateral membrane conductance of Necturus urinary bladder.

Abstract: Necturus urinary bladders stripped of serosal muscle and connective tissue were impaled through their basolateral membranes with microelectrodes in experiments that permitted rapid changes in the ion composition of the serosal solution . The transepithelial electrical properties exhibited a marked seasonal variation that could be attributed to variations in the conductance of the shunt pathway, apical membrane selectivity, and basolateral Na' transport .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…The ratio of resistances is also unchanged for several minutes after amiloride, which shows that basolateral membrane resistance initially increases with the same time course as that of the apical membrane.) Second, Ba", which blocks K+ conductance in a wide variety of tissues, including epithelia (Kirk et al, 1980 ;Latorre and Miller, 1983;Wills, 1985;Demarest and Finn, 1987), was found in the present study to block volume regulation . In keeping with this notion, Lewis et al (1985) have recently identified apparent volume-sensitive changes in basolateral membrane electromotive force and conductance in toad urinary bladder.…”
Section: Basolateral Membrane Solute Transport and Intracellular Ca ++supporting
confidence: 56%
See 1 more Smart Citation
“…The ratio of resistances is also unchanged for several minutes after amiloride, which shows that basolateral membrane resistance initially increases with the same time course as that of the apical membrane.) Second, Ba", which blocks K+ conductance in a wide variety of tissues, including epithelia (Kirk et al, 1980 ;Latorre and Miller, 1983;Wills, 1985;Demarest and Finn, 1987), was found in the present study to block volume regulation . In keeping with this notion, Lewis et al (1985) have recently identified apparent volume-sensitive changes in basolateral membrane electromotive force and conductance in toad urinary bladder.…”
Section: Basolateral Membrane Solute Transport and Intracellular Ca ++supporting
confidence: 56%
“…K' that is pumped into the cell is recycled across the basolateral membrane by electrodiffusion since the electromotive force in this, as in other, tight epithelia is primarily determined by K'. However, the membrane is not a perfect K' electrode, and, in fact, a Clconductance has been demonstrated in several tissues (Lewis et al, 1978;Wills et al, 1979;Thompson et al, 1982;Schultz et al, 1984;Demarest and Finn, 1987). Also incorporated into the model are features by which coordination of transport activities at the two membranes is achieved (see reviews by Taylor and lumen apical membrane blood FIGURE 1 .…”
Section: Introductionmentioning
confidence: 99%
“…"Leaky" epithelia have transepithelial resistances <300 f~ 9 cm 2 while "tight" epithelia have resistances >300 f~ 9 cm 2 (Diamond, 1979). The meafi transepithelial resistance in lingual epithelium from Necturus was 2000 -+ 1400 f~ 9 cm 2 (N = 24; mean -+ SD) when measured in symmetrical solutions of amphibian physiological saline (APS), comparable to that in urinary bladder from this species (Demarest & Finn, 1987a). This classifies Necturus lingual epithelium as tight.…”
Section: Resultsmentioning
confidence: 83%
“…The seasonal variation of the TEA-sensitive channels on the basolateral membrane was unexpected but not unprecedented. For example, the urinary bladder of Necturus also exhibits seasonal variations (Karnaky et al, 1984;Demarest & Finn, 1987a).…”
Section: Discussionmentioning
confidence: 99%
“…6 in Schultz, 1979). Using Necturus urinary bladder, Demarest and Finn (1987) found that the apical membrane potential became 40 mV more negative (i.e., hyperpolarized) upon doubling the paracellular resistance. In summary, the potential profiles across epithelial cells depends on the paracellular pathway(s) resistance and selectivity (Reuss, 1979;Schultz, 1979).…”
Section: Paracellular Pathways Between Taste Cellsmentioning
confidence: 97%